Comparison of hot water immersion at 37.8°C with or without salt for rapid weight loss in mixed martial arts athletes - Connor, J.; Shelley, A.; Egan, B. (Journal of Sports Sciences, 2020)
Hot water immersion, known as a hot bath, is used by MMA athletes to produce rapid weight loss (RWL) by means of passive fluid loss. This study investigated the magnitude of body mass losses using a standardized hot bath protocol with or without the addition of salt. In a crossover design, eleven male MMA athletes (28.5 ± 4.6 y; 1.83 ± 0.07 m; 82.5 ± 9.1 kg) performed a 20-min immersion at 37.8°C followed by a 40-min wrap in a warm room. This bath and wrap was performed twice per visit. During one visit, only fresh water was used (FWB), and in the other visit, magnesium sulphate (1.6% wt/vol) was added to the bath (SWB). Prior to each visit, 24 h of carbohydrate, fibre, and fluid restriction was undertaken as part of the RWL protocol. Body mass losses induced by the hot bath protocols were 1.63 ± 0.75 kg and 1.60 ± 0.80 kg for FWB and SWB, respectively, and equivalent to ~2.1% body mass. Under the conditions employed, the magnitude of body mass loss in SWB was similar to FWB. However, further research should explore bathing in a temperature that is consistent with that habitually used by fighters, and/or higher concentrations of salt.